2018
DOI: 10.5539/jas.v10n11p16
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Processing on Mungbean (Vigna radiata) Flour Nutritional Properties and Protein Composition

Abstract: Pulses are traditionally processed prior to consumption, providing opportunities for modifying nutritional composition, dependant on the type of pulse and method used. In this study, we investigated the effect of whole seed, dehulling (dahl), germination and roasting on changes in mungbean flour nutritional properties, protein composition and relative protein abundance. Processed flours were analysed and compared for protein content, moisture, fat, ash, dietary fibre, total starch and amylose. Significant diff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
3
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 36 publications
(39 reference statements)
4
3
0
4
Order By: Relevance
“…It has been reported that the protein content of cowpea, jack bean, dolichos, and mucuna also decreased after germination [26]. A total of 2195 proteins were identified (Additional file 1: Table S1), which were significantly more than the mung bean proteome reported in previous studies [6,27]. The types of proteins increased significantly after sprouting, which was in line with the result of Skylas et al [27].…”
Section: Analysis Of the Proteomic Profiles Of Mung Bean Seeds And Spsupporting
confidence: 84%
See 2 more Smart Citations
“…It has been reported that the protein content of cowpea, jack bean, dolichos, and mucuna also decreased after germination [26]. A total of 2195 proteins were identified (Additional file 1: Table S1), which were significantly more than the mung bean proteome reported in previous studies [6,27]. The types of proteins increased significantly after sprouting, which was in line with the result of Skylas et al [27].…”
Section: Analysis Of the Proteomic Profiles Of Mung Bean Seeds And Spsupporting
confidence: 84%
“…A total of 2195 proteins were identified (Additional file 1: Table S1), which were significantly more than the mung bean proteome reported in previous studies [6,27]. The types of proteins increased significantly after sprouting, which was in line with the result of Skylas et al [27]. During germination, storage proteins are hydrolyzed and de novo synthesis of proteins occurs, which are both necessary for the completion of seed germination [28].…”
Section: Analysis Of the Proteomic Profiles Of Mung Bean Seeds And Spsupporting
confidence: 67%
See 1 more Smart Citation
“…Whole mung bean flour (WMF) is more nutritious than cotyledon mung bean flour (CMF), and contains more than twice as much dietary fiber, about 10.6% (Skylas et al, 2018). But CMF has been more used, comprising 50% (Fathonah et al, 2020b) in gluten-free cookies (GF), 60% (Fathonah et al, 2018, 2020a) and 100% (Adair et al, 2001; Sakung et al, 2021) of the farinaceous ingredient in biscuit formulations.…”
Section: Introductionmentioning
confidence: 99%
“…The seeds are usually eaten whole, cooked or fermented, or milled into a flour [ 1 , 2 ]. The application of the flour is diverse and can be used to make noodles, bread, and other bakery products [ 3 , 4 , 5 , 6 ]. Mung bean generally contains significant amounts of protein, ranging from 18% to 36%.…”
Section: Introductionmentioning
confidence: 99%